Targeted set-aside: Benefits from reduced nitrogen loading in Danish aquatic environments. (1st October 2019) - Odgaard, Mette V.; Olesen, Jørgen Eivind; Graversgaard, Morten; Børgesen, Christen Duus; Svenning, Jens-Christian; Dalgaard, Tommy
Abstract: Nitrogen (N) leaching from agricultural areas in the form of nitrate (NO3 − ) is one of the most dominant sources of eutrophication in coastal waters. This environmental pressure is expected to intensify with the predicted increase in food demand, highlighting the need for developing novel ways to reduce N loads from agriculture. This may be achieved by exploiting the spatial variation in N removal through denitrification in groundwater and surface water systems. Thus, agricultural intensification should occur in areas characterized by high N removal potential, whereas effective N-reduction measures such as setting aside agricultural land (set-aside) should be targeted towards areas characterized by low N removal. Simultaneously, setting aside agricultural land can potentially strengthen local nature areas. To reach the water quality targets defined by the EU Water Framework Directive (WFD), the Danish region has defined individual coastal N reduction goals for each of the existing Danish water catchments. With set-aside as an effective N-reduction measure the study aims were to: 1) evaluate the effect of targeting areas to set aside versus using no targeting and 2) evaluate whether different prioritization for targeting set-aside areas enhances multi-functionality of the landscape, while efficiently achieving the required N load reduction. Areas were selected according to three priority values: 1) high contribution to coastal N loads, 2) high nature value, and 3) low agricultural land rent. The combination of these three values per area defined three multifunctional scenarios: ( GreenEnvi - N load dominates, TerreEco - nature dominates, AgroEcon - land rent dominates). Results indicate, that targeting areas with high N loads for set-aside is more beneficial (effective) for achieving multiple goals than blanket policies for entire countries (no targeting). Targeting requires only 23% of agricultural land compared to 35% when not targeting, leaving more land available for satisfying food demand. Moreover, multiple benefits can be achieved in surrounding environments by increasing set-aside to 25% according to the GreenEnvi scenario. The GreenEnvi scenario is also cheaper compared to targeting for only land rent. Highlights: The targeted method locate N sensitive areas based on N load, nature, and economy. Needed farm area were 23% when targeting for N loads, 36% for nature, 37% for economy. Targeting for best areas to set aside needs less agri-area vs no targeting (23–37%). There is a tradeoff between loss of agricultural area and environmental benefits.